A pilot study of active rehabilitation for adolescents who are slow to recover from sport-related concussion - Gagnon, I.; Grilli, L.; Friedman, D.; Iverson, G. L. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The purpose of this study was to examine the effectiveness of an active rehabilitation intervention for adolescents who are slow-to-recover after a sport-related concussion. Ten adolescents (three girls and seven boys) seen at the Montreal Children's Hospital Concussion Clinic participated in this case series. Adolescents who were symptomatic more than 4 weeks after the injury were provided with an active rehabilitation intervention (M = 7.9 weeks following injury; range = 3.7 to 26.2 weeks). The rehabilitation program includes gradual, closely monitored light aerobic exercise, general coordination exercises, mental imagery, as well as reassurance, normalization of recovery, and stress/anxiety reduction strategies. The program continued until complete symptom resolution and readiness to begin stepwise return to activities. The primary outcome of the study was evolution of post-concussion symptoms. Secondary outcomes included mood, energy, balance, and cognition. After the intervention, post-concussion symptoms significantly decreased for the group of participants. They also had decreased fatigue and improved mood after 6 weeks of initiating the rehabilitation intervention. This case series shows that postconcussive symptoms and functioning in adolescents following sports-related concussion can be improved after participation in an active rehabilitation intervention. The introduction of graded light intensity exercise in the post-acute period following concussion is safe, feasible and appears to have a positive impact on adolescents' functioning